Scribes and scribalism - Leuchter, Mark (The Hebrew Bible in social perspective, 2020)
Series Editor Preface / Francesca Stavrakopoulou, University of Exeter, UK -- Preface -- Abbreviations -- 1. Introduction: The Scholarly Context for the Study of Scribes and Scribalism / Mark Leuchter, Temple University, USA -- Part I: Praxis and Materiality -- 2. Influential Inscriptions: Resituating Scribal Activity During the Iron I-IIA Transition / Sarah Malena, St. Mary's College of Maryland, USA -- 3. The Media and Materiality of Southern Levantine Inscriptions: Production and Reception Contexts / Madadh Richey, University of Chicago, USA -- 4. Scribes and Scribalism in Archaic Crete / Anselm Hagedorn, University of Osnabrück, Germany -- Part II: Power and Status -- 5. Scribes, Schools, and Ideological Conflict in Ancient Israel and Judah -- Brian Rainey, Princeton Theological Seminary, USA -- 6. Ecclesiastes and the Problem of Transmission in Biblical Literature / Jacqueline Vayntrub, Yale Divinity School, USA -- 7. Textualization and the Transformation of Biblical Prophecy / Heath D. Dewrell, Princeton Theological Seminary, USA -- 8. Reorientation in Responsibility of Levites Taking care for the Ark: The Levites' Role in Samuel-Kings in Relation to Deuteronomistic Expressions Concerning Interpretation of the Law / Antje Labahn, Wuppertal Hochschule, Germany -- Part III: Between Ideology and Authority -- 9. Writing in Three Dimensions: Scribal Activity and Spaces in Jewish Antiquity / Laura Carlson Hasler, Indiana University, USA -- 10. Rejecting 'Patriarchy': Reflections on Feminism, Biblical Scholarship, and Social Perspective -- Shawna Dolansky, Carleton University, Canada -- Bibliography -- Indexes